2013
DOI: 10.5194/bg-10-4009-2013
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, distribution and spatial structure of the cold-water coral fauna of the Azores (NE Atlantic)

Abstract: Cold-water corals are widely considered as important structural components of benthic habitats, potentially enhancing local abundance in a variety of fish and invertebrate species. Yet, current knowledge of the taxonomic diversity and distribution patterns of these vulnerable, slow-growing organisms is scarce and fragmented, limiting the effectiveness of spatial management and conservation measures. We have conducted an exhaustive compilation of records of alcyonaceans, antipatharians, scleractinians and styla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 88 publications
2
37
0
Order By: Relevance
“…Common topographic features of the Azorean deep sea are island slopes, seamounts, hydrothermal vents and abyssal plains, the latter sometimes achieving more than 3200 m depth. The topographically rich seafloor is estimated to represent 37% of the EEZ with extreme importance for the open ocean and the deep-sea habitats containing a high diversity of pelagic and benthonic animals, living or visiting the Azorean archipelago (Morato et al 2013;Braga-Henriques et al 2013, Vandeperre et al 2014. In this work, the area of study was delimited by a rectangle box between 3336´N-436´N (DM) and 3536´W-2051´W (DM) enclosing the EEZ of the Archipelago (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Common topographic features of the Azorean deep sea are island slopes, seamounts, hydrothermal vents and abyssal plains, the latter sometimes achieving more than 3200 m depth. The topographically rich seafloor is estimated to represent 37% of the EEZ with extreme importance for the open ocean and the deep-sea habitats containing a high diversity of pelagic and benthonic animals, living or visiting the Azorean archipelago (Morato et al 2013;Braga-Henriques et al 2013, Vandeperre et al 2014. In this work, the area of study was delimited by a rectangle box between 3336´N-436´N (DM) and 3536´W-2051´W (DM) enclosing the EEZ of the Archipelago (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Antipatharians are colonial hexacorals reported to present longevities ranging from decades to millennia (Carreiro-Silva et al 2013;Love et al 2007;Roark et al 2009), and occurring between 20 and 5440 m (Gravier 1921;Braga-Henriques et al 2013) in the Northeast Atlantic Ocean. This taxon was generally assumed to be azooxanthellate, due to a preference for low-light environments that do not allow photosynthesis, but recently, several species occurring at up to 396 m of depth were shown to associate with Symbiodinium (Bo et al 2011;Wagner et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The afore mentioned turbulent ENACW-MOW boundary might allow the transport of coral larvae along the NE Atlantic margins (Somoza et al, 2014). At the Mid Atlantic Ridge, the Azores region hosts an exceptional biodiversity of CWCs (Figure 2), mostly gorgonians (75% of the octocoral species of European waters), with a greater affinity to the Lusitanian-Mediterranean biogeographic region (71% shared species) and to a lesser extent to the NW Atlantic (Braga-Henriques et al, 2013;Sampaio et al, 2019). The presence of multiple intermediate and deep water masses (NACW, subpolar origin waters, MOW, AAIW, NADW; Johnson and Stevens, 2000;Amorim et al, 2017) along the slopes of many seamounts are hypothesized to shape composition and bathymetrical distribution of coral gardens in the Azores (Braga-Henriques et al, 2013).…”
Section: Cold-water Coral Reefs and Gardensmentioning
confidence: 99%
“…At the Mid Atlantic Ridge, the Azores region hosts an exceptional biodiversity of CWCs (Figure 2), mostly gorgonians (75% of the octocoral species of European waters), with a greater affinity to the Lusitanian-Mediterranean biogeographic region (71% shared species) and to a lesser extent to the NW Atlantic (Braga-Henriques et al, 2013;Sampaio et al, 2019). The presence of multiple intermediate and deep water masses (NACW, subpolar origin waters, MOW, AAIW, NADW; Johnson and Stevens, 2000;Amorim et al, 2017) along the slopes of many seamounts are hypothesized to shape composition and bathymetrical distribution of coral gardens in the Azores (Braga-Henriques et al, 2013). Braga-Henriques et al, 2013 reported maximum Antipatharian diversity at 400-500 m coinciding with the cold and less dense NACW; whilst the maximum diversity of Alcyonacea (e.g., Viminella flagellum, D. meteor, Callogorgia verticillata, and A. armata) occurs at 500-600 m coinciding with the less saline subpolarorigin waters.…”
Section: Cold-water Coral Reefs and Gardensmentioning
confidence: 99%